PELESAPAN PARTIKEL DALAM BAHASA JEPANG - Reny Wiyatasari (KIRYOKU, 2017)
There are different types of particles in Japanese. These particles play a role in determining the relationships between words that make up a sentence and also play a role in determining the meaning of a sentence. Nevertheless, the particles are often deliberately eliminated in conversation. This article aims to explain about some particles that are often eliminated in the language of the conversation, how it can happen, and when the use of such particles is absolutely necessary. The data are collected from textbooks and children's stories containing sentences that have particle elimination. In this article, based on data collection , there are five types of particles that are most often eliminated: ga, o, wa, e, and ni. From the analysis results, most of the elimination occurs in speech or verbal sentences that are spoken in informal situations. Although eliminated, it did not cause misunderstandings related to the meaning of a speech because the particle elimination will not affect communication. This is because the speakers already have the same background knowledge related to the topic of conversation.